Tetraacylgermanes: Highly Efficient Photoinitiators for Visible‐Light‐Induced Free‐Radical Polymerization. Issue 11 (3rd February 2017) - Radebner, Judith; Eibel, Anna; Leypold, Mario; Gorsche, Christian; Schuh, Lukas; Fischer, Roland; Torvisco, Ana; Neshchadin, Dmytro; Geier, Roman; Moszner, Norbert; Liska, Robert; Gescheidt, Georg; et al.
Abstract: In this contribution a convenient synthetic method to obtain tetraacylgermanes Ge[C(O)R]4 (R=mesityl (1 a ), phenyl (1 b )), a previously unknown class of highly efficient Ge‐based photoinitiators, is described. Tetraacylgermanes are easily accessible via a one‐pot synthetic protocol in >85 % yield, as confirmed by NMR spectroscopy, mass spectrometry, and X‐ray crystallography. The efficiency of1 a, b as photoinitiators is demonstrated in photobleaching (UV/Vis), time‐resolved EPR (CIDEP), and NMR/CIDNP investigations as well as by photo‐DSC studies. Remarkably, the tetraacylgermanes exceed the performance of currently known long‐wavelength visible‐light photoinitiators for free‐radical polymerization Abstract : "Molar" solutions : Germanium‐based photoinitiators for light‐induced radical polymerization outperform the established initiator systems, especially for applications in the long‐wavelength range, of particular interest in the dental industry.